Pt- and TCO-free flexible cathode for DSSC from highly conducting and flexible PEDOT paper prepared via in situ interfacial polymerization - Anothumakkool, Bihag; Agrawal, Ishita; Bhange, Siddheshwar N.; Soni, Roby; Game, Onkar S.; Ogale, Satishchandra B.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2016)
Here, we report the preparation of a flexible, free-standing, Pt- and TCO-free counter electrode in dye-sensitized solar cell (DSSC)-derived from polyethylenedioxythiophene (PEDOT)-impregnated cellulose paper. The synthetic strategy of making the thin flexible PEDOT paper is simple and scalable, which can be achieved via in situ polymerization all through a roll coating technique. The very low sheet resistance (4 Omega/square) obtained from a film of 40 mu m thick PEDOT paper (PEDOT-p-5) is found to be superior to the conventional fluorine-doped tin oxide (FTO) substrate. The high conductivity (357 S/cm) displayed by PEDOT-p-5 is observed to be stable under ambient conditions as well as flexible and bending conditions. With all of these features in place, we could develop an efficient Pt- and TCO-free flexible counter electrode from PEDOT-p-5 for DSSC applications. The catalytic activity toward the tri-iodide reduction of the flexible electrode is analyzed by adopting various electrochemical methodologies. PEDOT-p-5 is found to display higher exchange current density (7.12 mA/cm(2)) and low charge transfer resistance (4.6 Omega) compared to the benchmark Pt-coated FTO glass (2.40 mA/cm(2) and 9.4 Omega, respectively). Further, a DSSC fabricated using PEDOT-p-5 as the counter electrode displays a comparable efficiency of 6.1% relative to 6.9% delivered by a system based on Pt/FTO as the counter electrode.
Keywords: counter electrode; dye-sensitized solar cell; flexible and thin devices; impedance analysis; interfacial polymerization; polyethylenedioxythiophene

Phenothiazine-based D-A-π-A dyes for highly efficient dye sensitized solar cells: effect of internal acceptor and non-conjugated π-spacer on device performance - Nagane, Satyawan; Ichake, Amol; Agrawal, Ishita; Sadhanala, Aditya; Friend, Richard H.; Ogale, Satishchandra; Wadgaonkar, Prakash P. (ChemPlusChem, 2017)
Three new D-A-pi-A metal-free organic dyes based on phenothiazine as a donor (D) and non-conjugated pi-spacer were designed and synthesized. The incorporation of different 'internal acceptors' (electron traps) such as benzothiadiazole (BTD), benzotriazole (BTA), and pyridine were shown to allow systematic tuning of the energy levels and the photophysical properties. The AI-1 dye showed lower electronic disorder compared with the other two dyes. The efficiencies achieved with AI-1, AI-2, and AI-3 dyes were 8.5% (J(sc) = 15.42 mA cm(-2), V-oc = 0.78 V, FF = 68%), 7% (J(sc) = 12.8 mA cm(-2), V-oc = 0.78 V, FF = 68%) and 6.7% (J(sc) = 11.57 mA cm(-2), V-oc = 0.82 V, FF = 68.26 %), respectively. The incorporation of non-conjugated phenothiazine as a p-spacer in D-A-pi-A dyes showed remarkable enhancement in the photovoltaic performance of dye-sensitized solar cell (DSSC) devices. The sealed DSSC devices with iodide/tri-iodide (I-/I-3(-) @)based liquid electrolyte showed promising stability under ambient conditions.